Interscorer reliability of the MMPI-2: should TRIN and VRIN be computer scored? - Iverson, Grant L.; Barton, Elizabeth (Journal of Clinical Psychology, 1999)
Some clinicians and researchers hand score their MMPI-2 protocols. Graham (1990) noted that TRIN and VRIN involve complex scoring that is best done by a computer. We examined the interscorer reliabilities of TRIN and VRIN and compared these results to the reliabilities of the other validity and clinical scales. Despite the high reliabilities (.97 to 1.00) clerical errors were common (i.e., 7% of the scales were scored inconsistently). Graham's caution about the inherent difficulty of scoring VRIN, but not TRIN was supported. There were three times as many scoring disagreements for VRIN than any other scale (i.e., 27% of the protocols were in disagreement). Reprinted by permission of the publisher.